Nonmarine time-stratigraphy in a rift setting: An example from the Mid-Permian lower Quanzijie low-order cycle Bogda Mountains, NW China - Obrist-Farner, Jonathan; Yang, Wan; Hu, Xiu-Fang (Journal of Palaeogeography, 2015)
AbstractSedimentological and stratigraphic studies of seven stratigraphic sections of Permian Hongyanchi (HYC) and Quanzijie (QZJ) low-order cycles (LCs) in the Tarlong-Tao-donggou half graben and Dalongkou area in Bogda Mountains, NW China, demonstrate effec-tive approaches and methodology in cyclo- and time-stratigraphic analyses of complex lfuvial-lacustrine deposits in an intracontinental rift setting. A new synchronous stratigraphic unit, the lower QZJ LC is deifned. The lower and upper boundaries of this cycle include a regionally correlative disconformity, erosional unconformity, and conformity, across which signiifcant and abrupt changes in palaeoenvironments and tectonic and climatic conditions occurred. The lower boundary is an erosional unconformity and disconformity with a high-relief topography that juxtaposes lacustrine deposits of the underlying HYC LC with the overlying meandering stream deposits of the lower QZJ LC, and was caused by a regional tectonic uplift. The up-per boundary is a disconformity and local erosional unconformity and conformity, juxtaposing stacked paleosols developed on lfuvial sediments with overlying lfuvial and loessial deposits of the upper QZJ LC. The paleosols indicate landscape stability and a prolonged period of subaerial exposure and minimal deposition and suggest that climatic conditions were semi-arid with strong precipitation seasonality in the Tarlong-Taodonggou half graben and subhumid in the Dalongkou area. The lfuvial-loessial deposits indicate a renewed tectonic uplift and a change in the atmospheric circulation pattern. The newly-deifned lower QZJ LC facilitates accurate palaeogeographic reconstruction in the study area during a period of major tectonic and climatic changes. The interpreted tectonic and climatic conditions provide a critical data point in the mid-latitude east coast of NE Pangea during the Mid-Permian icehouse-hothouse transition. The results demonstrate that a process-response approach is effective in time-stratigraphic analysis of complex lfuvial-lacustrine strata in a highly-partitioned rift basin.